(untitled) (Journal of Education and Development, 2025)
Using two independent academic cohorts, i.e., Fall 2021-Spring 2022 (n = 356) and Fall 2022-Spring 2023 (n = 180), of graduating business students, the relationships of three perceived curriculum-improved abilities (CA) scales and an employment applicable skills (EAS) scale to type of business major satisfaction were tested. Quantitative versus qualitative majors were separated. Confirmatory factor analyses verified the three-scale structure of the 12-item CA measure as: Business Problem Solving (6 items); Presentation Skills (3 items) and Team-related Skills (3 items). Regression results indicated that Business Problem Solving had a positive relationship to quantitative major satisfaction, while EAS was related to qualitative major satisfaction. Open item analyses converged with these results.